Immune Responses to rAAV6: The Influence of Canine Parvovirus Vaccination and Neonatal Administration of Viral Vector - Arnett, Andrea L.; Garikipati, Dilip; Wang, Zejing; Tapscott, Stephen J.; Chamberlain, Jeffrey S. (Frontiers in Microbiology, 2011)
Recombinant adeno-associated viral (rAAV) vectors promote long-term gene transfer in many animal species. Significant effort has focused on the evaluation of rAAV delivery and the immune response in both murine and canine models of neuromuscular disease. However, canines provided for research purposes are routinely vaccinated against canine parvovirus (CPV). rAAV and CPV possess significant homology and are both parvoviruses. Thus, any immune response generated to CPV vaccination has the potential to cross-react with rAAV vectors. In this study, we investigated the immune response to rAAV6 delivery in a cohort of CPV-vaccinated canines and evaluated multiple vaccination regimens in a mouse model of CPV-vaccination. We show that CPV-vaccination stimulates production of neutralizing antibodies with minimal cross-reactivity to rAAV6. In addition, no significant differences were observed in the magnitude of the rAAV6-directed immune response between CPV-vaccinated animals and controls. Moreover, CPV-vaccination did not inhibit rAAV6-mediated transduction. We also evaluated the immune response to early rAAV6-vaccination in neonatal mice. The influence of maternal hormones and cytokines leads to a relatively permissive state in the neonate. We hypothesized that immaturity of the immune system would permit induction of tolerance to rAAV6 when delivered during the neonatal period. Mice were vaccinated with rAAV6 at 1 or 5 days of age, and subsequently challenged with rAAV6 exposure during adulthood via two sequential IM injections, 1 month apart. All vaccinated animals generated a significant neutralizing antibody response to rAAV6-vaccination that was enhanced following IM injection in adulthood. Taken together, these data demonstrate that the immune response raised against rAAV6 is distinct from that which is elicited by the standard parvoviral vaccines and is sufficient to prevent stable tolerization in neonatal mice.